Is the Chinese investment- and export-led growth model sustainable? Some rising concerns - Arslan Razmi (University of Massachusetts, Department of Economics, 2008)
China's rapid growth and success in poverty reduction over the last three decades has inspired world-wide admiration. This paper uses a simple framework with a Kaleckian flavor to analyze structural developments in the Chinese economy, and to understand some of the distributional consequences. Some of the possible sources of these distributional developments are then further analyzed using a trade-theoretic approach. Other aspects of China's investment- and export-led growth strategy are discussed along with the problems that the focused pursuit of such a strategy has raised. We conclude that China's growth model may now have outlived its utility, both on economic and socio-political grounds.
Keywords: 330; Wirtschaftswachstum; Wachstumspolitik; Exportinduziertes Wachstum; China; Kritik